2006
DOI: 10.1037/1076-8998.11.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and preventing supervisory workplace aggression.

Abstract: The authors examined factors that lead to and prevent aggression toward supervisors at work using two samples: doctoral students and correctional service guards. The results supported that perceived interpersonal injustice mediates the relationship between perceptions of supervisory control over work performance and psychological aggression directed at supervisors, and further that psychological aggression toward supervisors is positively associated with physical acts of aggression directed at supervisors, sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 87 publications
5
71
0
1
Order By: Relevance
“…Moreover, over-controlling supervision accounted for 2.7% of the unique variance in embitterment. Dupré and Barling, (2006), found that excessive control over employees' performance may have a detrimental influence on employees. When employees are subject to controlling supervision, they may feel unjustly treated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, over-controlling supervision accounted for 2.7% of the unique variance in embitterment. Dupré and Barling, (2006), found that excessive control over employees' performance may have a detrimental influence on employees. When employees are subject to controlling supervision, they may feel unjustly treated.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars such as Dupré and Barling (2006), have considered over-controlling supervision as a form of organisational injustice. When subordinates perceive that their work performance is highly controlled by their supervisors they perceive this is a lack of respect, dignity and courtesy, and thus they are likely to experience organisational injustice (Tyler and Bies, 1990).…”
Section: Hypothesis 1cmentioning
confidence: 99%
See 2 more Smart Citations
“…This becomes especially important when one considers that victims of aggression may, in some instances, perceive their mistreatment to be a function of their sex, race, or other protected characteristic, as this could lead victims to take legal action against the organization. Organizations must make greater efforts to create policies that prohibit workplace aggression (Dupré & Barling, 2006), to ensure that such policies are communicated and understood, and that appropriate investigation and enforcement ensues (Hershcovis & Barling, 2006). Doing so would benefit both organizations and their members.…”
Section: Practical Implicationsmentioning
confidence: 99%